User-producer interaction in the Brazilian oil industry: The relationship between petrobras and its suppliers of wet Christmas tree - Guimarães Gielfi, Giovanna; Pereira, Newton Müller; Gomes, Rogerio [UNESP]; Fornari, Vinícius Cardoso de Barros [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2013)
The objective of this work is to analyze the importance of the user-producer interaction for the innovative process of the Brazilian oil industry from the 2000s. To do so, we selected two of the three providers installed in Brazil that produce the set of valves used in the oil wellhead to control its production, set which is called wet Christmas tree (WCT), the Norway's Aker Solutions and the American FMC Technologies. The results of this analysis indicate not only the development of the oil industry in Brazil is marked by a strategy of cooperative innovation, but they also reveal the importance of geographical proximity and direct cooperation, especially between the centers of engineering and research and development of companies. Furthermore, these partnerships are not limited to the adaptation of products to new needs, but they also include the development of new systems. © Universidad Alberto Hurtado, Facultad de Economía y Negocios.
Keywords: Innovation; Oil industry; Petrobras; User-producer relationship